PENGARUH GAYA HIDUP DAN PENDAPATAN TERHADAP PERILAKU KONSUMTIF YANG DIMODERASI OLEH KONTROL DIRI (Studi Kasus PNS Kemenag Kab. Pasaman) - rahmita, Elchi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
This study aims to determine the effect of lifestyle and income on consumptive behavior moderated by self-control in civil servants of the Ministry of Religion of Kab. Passover. The research was motivated by changes in the consumptive behavior of Ministry of Religion civil servants which decreased in 2 years when seen from the decrease in the graphic of PNS consumptive loans at the Ministry of Religion Civil Servant Cooperative Kab. Passover. This study uses a quantitative approach. By using a questionnaire distributed to 45 civil servants in the Ministry of Religion of Kab. Passover. With a saturated sampling technique that has the criteria of all civil servants in the Ministry of Religion Office of Kab. Passover. Instrument testing in this study used validity and reliability tests, data analysis techniques used descriptive analysis, used the classic assumption test consisting of multicollinearity tests, heteroscedasticity tests and normality tests, as well as moderation regression analysis. The results of this study indicate that: (1) Lifestyle has a significant effect of 0.002 <0.05; (2) Income has a significant effect of 0.000<0.05; (3) Self-control has a negative effect on Lifestyle and Consumptive Behavior with a t-value of -1.976 and a significance of 0.001<0.05; (4) Self-control has a negative effect on income and consumptive behavior with a t-value of -1.984 and a significance value of 0.002 <0.05.